Low-Frequency Dual-Band Sound Absorption by Ultrathin Planar Wall Embedded With Multiple-Cavity Resonators - Xu, Yu-wei; Guan, Yi-jun; Yin, Jia-li; Ge, Yong; Sun, Hong-xiang; Yuan, Shou-qi; Liu, Xiao-jun (Frontiers in Physics, 2022)
We report the numerical and experimental realization of a type of ultrathin planar wall with low-frequency dual-band sound absorption. The proposed planar wall is constructed by a periodic subwavelength unit cell (with a thickness of λ/19) which consists of two different multiple-cavity resonators embedded into a plate structure with a groove. The sound absorption of the wall exists in two working bands below 600 Hz which are created by two different mechanisms, such as a mutual coupling of two eigenmodes of multiple-cavity resonators and the eigenmode of a whole structure of the unit cell, and the fractional bandwidths of both bands can reach about 34.1% and 10.4%. Furthermore, the application of the proposed ultrathin planar wall in the design of a barrier-free anechoic room with omnidirectional low-frequency dual-band sound absorption is further discussed in detail. The proposed planar wall has the advantages of ultrathin planar structure and omnidirectional low-frequency dual-band sound absorption, which provides diverse routes to design advanced sound-absorption structures in noise control and architectural acoustics.